Martahi Martulpak Tradition: Living Hadith as a Means of Shaping Social and Cultural Norms of the Mandailing Community - Harahap, Alwi Padly; Siregar, Hakkul Yakin; Rahmi, Tutia; Hasibuan, Maulana Hasan; Siregar, Rois Hamid; Akbar, Fauzan (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The Martahi Martulpak tradition in Mandailing society is a collective practice that reflects the value of mutual assistance in supporting the costs of organizing a wedding. Although it has been widely studied as part of local culture, limited research has linked this practice to the concept of living hadith, particularly to actualise Islamic values in a social context. This study aims to fill the theoretical gap regarding how the values of the hadith about ta'āwun (mutual assistance), ukhūwah (brotherhood), and alms are actualized in local cultural practices. Using descriptive qualitative methods and participatory observation techniques as well as in-depth interviews, this study explores the social and religious meaning of Martahi Martulpak for the Mandailing community. The study results show that Martahi Martulpak not only represents the socio-cultural values of Mandailing but also actualizes the teachings of the hadith in a local context. This tradition reflects the practice of collective alms and mutual assistance, where community participation is not only based on social obligations but is also interpreted as worship. This participation strengthens the bonds of brotherhood, strengthens the social structure, and expands the meaning of hadith in the social realm. Thus, Martahi Martulpak becomes a reflection of the living hadith, which is dynamic, adaptive, and contextual in forming the social and spiritual norms of the Mandailing community.